DISKURSUS LOGIKA DAN PENALARAN DALAM MENGEMBANGKAN KEMAMPUAN BERPIKIR KRITIS - M. Husnullail; Ahmad Syukri; Maryani; Asbui; Deassy Arestya Saksitha Pulungan (Jurnal Genta Mulia, 2024)
Logic is a branch of philosophy that explores rules, principles, legal books, and methods or procedures in achieving knowledge rationally and correctly. It is also a way to acquire knowledge using systematic reasoning, words, and language. Logic can be systematized into several categories depending on the perspective from which we view it. In terms of quality, logic can be distinguished into two, namely natural logic and artificial logic (scientific logic). Reasoning is a critical thinking process in drawing conclusions that result in knowledge. Humans are fundamentally creatures that think, feel, behave, and act. Attitudes and actions are based on knowledge obtained through feeling or thinking activities. Reasoning produces knowledge associated with critical thinking activities. Reasoning is a critical thinking process in drawing conclusions that result in knowledge. Therefore, reasoning is one of the processes in critical thinking that combines two or more thoughts to draw a conclusion to gain knowledge.